Percepções de diretores escolares sobre formação no município de Dourados/MS: relação entre saberes e práticas - Nascimento, Taynara Tavares do (2022)
This paper is related to the Programa de Pós-Graduação em Educação (PPGEdu) of the Universidade Federal da Grande Dourados (UFGD), to the research line of Policies and Education Management and to the Grupo de Pesquisa Estado, Política e Gestão da Educação (GEPGE). The research is also associated with the project “Concepções dos Diretores das Escolas de Educação Básica de Dourados sobre a Gestão Escolar”. This paper aimed to analyze the academic education profile and the perceptions for school principals about the initial and continuing education directed to school management, related to their performance in the municipality of Dourados/MS, as well as to verify the existence of actions in the municipality of education for these professionals. It is intended to identify elements of continuing education that contribute to the performance of principals. The research has a qualitative approach and the methodological path adopted was bibliographic, documentary and fieldwork through interviews with the principals of the selected schools. Eight principals of urban schools were interviewed. As for the academic education profile, it was found that most professionals have the Pedagogy course as their initial education, with experiences of at least ten years and active throughout their professional career in the school where they have the function of school principals, which demonstrates the need for proximity to the school community. It was found that school principals consider that initial academic education allows basic knowledge about the function, which is learned in practice. Continuing education is perceived as fundamental and a demand from principals, for education that addresses themes relevant to the local reality, such as administrative and pedagogical issues. Thus, it appears that although the principals have the perception of the need for continuing education aimed at school management, there is no education policy in the municipality for these professionals. In this way, the learning of the function occurs in practice and in individual searches for training.